Bugs A to Z - DeGezelle, Terri (Mankato, MN Capstone Curriculum Publ, 2000)
Introduces the world of bugs through photographs and facts which describe one for each letter of the alphabet.
Keywords: Insects -- Juvenile literature; Arthropoda -- Juvenile literature; English language alphabet -- Juvenile literature